AN ANALYSIS OF STUDENTS’ LEARNING STRATEGIES IN SPEAKING - Jernih D. Sinurat (Journal MELT (Medium for English Language Teaching), 2021)
This study attempted to analyze the students’ learning strategies in speaking. The purpose of the study is to describe the types of speaking learning strategies, the dominant ones. It was presented a qualitative descriptive research. The sources of data were taken from students of Potensi Utama University which located at Jl.K.L.Yos Sudarso, Km. 6.5 No. 3A Tanjung Mulia Medan. Twenty three students’ were taken as subject of this research. The data were collected by used questionnaire. Based on the obtained information, the data were analyzed. The data analysis found out the findings indicates that were 6 learning strategies (memory strategy, cognitive strategy, compensation strategy, meta-cognitive strategy, affective strategy, social strategy) in speaking by the students. They were used; 3students (13%) in memory strategy; 13students, (57%) in cognitive strategy; 3students (13%) in compensation strategy; 1student (4%) in meta-cognitive strategy; 2students (9%) in affective strategy; 1student (4%) in social strategy. It was found that, cognitive strategy was dominantly applied. The finding shows that this study has significance implications in teaching and learning English especially in speaking for specific purposes. Finally, the finding shows that six learning strategies was finding in the students’ speaking. It is proved that the students have fulfilled the standard in certain speaking learning strategies as stated by Oxford (1990).